2004
DOI: 10.1115/1.1914803
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Simulations of Nozzle Flow, Primary Fuel Jet Breakup, and Spray Formation

Abstract: Presented are two approaches for coupled simulations of the injector flow with spray formation. In the first approach the two-fluid model is used within the injector for the cavitating flow. A primary breakup model is then applied at the nozzle orifice where it is coupled with the standard discrete droplet model. In the second approach the Eulerian multi-fluid model is applied for both the nozzle and spray regions. The developed primary breakup model, used in both approaches, is based on locally resolved prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Thus, the measurement of the momentum flux can be combined with the injection rate to derive the velocity at the nozzle exit [7] [8]. Also, the influence of nozzle geometry on the internal flow characteristics of a diesel injector has been carried out with a simulation analysis [9]- [12]. The simulation studies confirm the tendency observed in experiments, that the nozzle geometry significantly influences the inner flow characteristics.…”
Section: Introductionsupporting
confidence: 61%
“…Thus, the measurement of the momentum flux can be combined with the injection rate to derive the velocity at the nozzle exit [7] [8]. Also, the influence of nozzle geometry on the internal flow characteristics of a diesel injector has been carried out with a simulation analysis [9]- [12]. The simulation studies confirm the tendency observed in experiments, that the nozzle geometry significantly influences the inner flow characteristics.…”
Section: Introductionsupporting
confidence: 61%
“…Here, the spray contours were determined by the limiting threshold values for the liquid volume fraction and the vapour mass fraction. More details about the determination process of the limiting threshold values can be found in [40]. In our work, the liquid tip penetration was defined as the furthest distance of the liquid phase where the total liquid volume fraction accounts for 0.1% of the control volume.…”
Section: Resultsmentioning
confidence: 99%
“…The coefficients used within the atomisation models are presented by Eqs. (14)- (17), whilst the break-up model details are described in [40]. The definition of the harmonic turbulent/aerodynamic time scale combination is shown in [34].…”
Section: Eulerian Multiphase Approachmentioning
confidence: 99%
“…The state of bubble diameter is a function of position and time (poly-dispersed diameter); coalescence due to turbulent random collisions, breakup (induced by turbulent impact) and bubble generation due to cavitation are the mechanisms taken into account. The complete mathematical description of this approach in the modeling of multiphase nozzle flow has been published and can be found in [44,45]; these authors also report the model validation against several reference flows.…”
Section: Multiphase Nozzle Flow Modelingmentioning
confidence: 99%
“…To allow the comparison among the holes, the results of the nozzle CFD model have been lumped in non-dimensional parameters that qualify the flow at each outlet section [45]. In the adopted scheme, Equation (16), the liquid-phase mass flow rate (m r ) passes through an effective area (A e ) with a uniform velocity (v e ); thus, vena contracta and cavitation affect the flow reducing the geometrical area (A g ) to the effective one (A e ).…”
Section: Non-dimensional Coefficientsmentioning
confidence: 99%